Unwanted, rejected, unaccepted: around the problem of “invisible” Romani and Dom children in Georgia - Urszula Markowska-Manista (Problemy Wczesnej Edukacji, 2015)
The text outlines fragments of Georgian Romani and Dom children’s reality through the prism of their everyday life and educational practices. Romani (or Roma) and Dom children are usually perceived by the majority of society as well as by national and ethnic minorities as an identical, uniform group. Their images are burdened with stereotypes and they themselves – as begging participants in public space – have become inconvenient for the majority of the society, hence excluded and marginalized. With regard to social representations, Roma and Dom children can be included in the category of “street children”, children “out of place”, “invisible” children, and children remaining “at the crossroads” of tradition and postmodernity. A portrayal of the situation of Roma and Dom minorities in Georgia reveals the reality of children in big city environments as well as the dimensions of their social exclusion and poverty. The text was written within field research: “The forgotten minorities in Georgia” conducted by the author in 2013 and 2014 in Georgia, South Caucasus.